Multicultural Art Nouveau Décor and Polychromy in the Interior of the Chaim Frenkel Villa in Šiauliai - Preišegalavičienė Lina (Meno Istorija ir Kritika, 2022)
The Frenkel family was famous in Lithuania not only as major manufacturers but also as generous benefactors. They honourably fulfilled the duty of a wealthy Jew to provide charity and social assistance to those most in need. The Frenkel family was forced to leave Lithuania in 1939: during the Soviet and Nazi occupations, the family lost all their possessions. While some family members had Lithuanian citizenship, the property rights of the descendants of Chaim Frenkel (1857–1920) were not reinstated, and from 17 June 1993 the Chaim Frenkel Villa became a department of the Šiauliai “Aušros” Museum (ŠAM, established in 1923). After the building’s renovation (finished in 2008) the villa’s interior spaces reflect minimally survived aesthetics of high class everyday Lithuanian Jewish private life at the beginning of the 20th century. The aim of the article is to argue how the Art Nouveau style in (territory of nowadays) Lithuania was not pure, but intertwined with retro-styles and internationalism. The case of the Ch. Frenkel Villa enriches the history of Lithuanian Art Nouveau with rich combinations of colours, shapes and compositions typical of Lithuanian Jews. Noticeably in the case of the Ch. Frenkel Villa, the traditionalist way of life and the wisdom of Jewish daily life restrained fashionable European design innovations. This is proof that the living environment of Lithuanian Jews was perceived as an important space for spiritual life and the worship of God.